Sistem Informasi Pembayaran SPP dan Tabungan Siswa Berbasis Web di SMP Putra Bangsa - Herpiah Herpiah; Muhammad Rifky Zulkarnaen; Joko Prasetyo; Wasis Haryono (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The manual payment system for Education Development Contributions (SPP) and student savings at SMP Putra Bangsa faces various obstacles, such as recording errors, loss of proof of payment, and difficulty tracking transaction history. This study aims to develop a web-based information system to overcome these problems. The research method involves needs analysis, system design using the Unified Modeling Language (UML), and web-based implementation. The results show that the designed system can simplify the transaction process, improve recording accuracy, and provide transparent access for students, homeroom teachers, and administration. This system is also able to produce real-time financial reports to support management decision making.